Effects of pemafibrate on primary biliary cholangitis with dyslipidemia - Yamaguchi, Mayumi; Asano, Takeharu; Arisaka, Takahiro; Mashima, Hirosato; Irisawa, Atsushi; Tamano, Masaya (Hepatology research, 2022)
Aim The purpose of this study was to examine the effect of pemafibrate (PEM) in primary biliary cholangitis (PBC) patients with dyslipidemia. Methods Patients who were diagnosed with PBC between June 2018 and December 31, 2020 were included in the study if they also had dyslipidemia and their alkaline phosphatase (ALP) or gamma‐glutamyl transferase (GGT) levels remained above the normal range despite taking 600 mg/day ursodeoxycholic acid (UDCA) for at least 6 months. Patients who were treated with UDCA alone were administered PEM as an add‐on (PEM‐add group), and patients who were treated with UDCA and bezafibrate (BEZ) for at least 6 months were given PEM instead of BEZ (PEM‐switch group). Clinical parameters were compared in all patients, and the levels of ALP, GGT, the estimated glomerular filtration rate (eGFR), and creatinine (Cr) were compared between the PEM‐add and PEM‐switch groups. Improvement in cholangitis was also evaluated. Results In the PEM‐add group, both ALP and GGT improved in 40 of 46 patients (87.0%). In the PEM‐switch group, both ALP and GGT improved in 15 of 29 patients (51.7%). In the PEM‐switch group, however, significant improvement was seen in eGFR and Cr. Conclusions Administration of PEM is effective in PBC patients with dyslipidemia who are refractory to UDCA monotherapy. In patients using both UDCA and BEZ, there was an advantage in switching to PEM if they had renal damage; however, improvement of ALP and GGT occurred in about 50%.